Clinical Presentation and Histopathological Pattern of Breast Lesions: A Five Years’ Single Center Experience (Tanzania Medical Journal, 2020)
BackgroundBreast lesions are very common and vary across the age in both females and males. Breast lesions constitute the commonest indication for breast surgery in women. The clinical presentation mirrors the underlying condition. Understanding local profile of breast lesions is an essential component in patients’ management decision making and resource allocation. This study was conducted to determine local clinical and cytohistopathological pattern of breast lesions seen in Dodoma for a period of five years from 2011 to 2015.MethodsRetrospective descriptive chart review of breast specimens and cytology submitted for cytohistopathological examination for a period of five years. Data extraction sheet was used to collect clinical and cytohistopathological information from the available laboratory master sheet. Information such as demographic factors, clinical presentation, cytological, and histopathological results were obtained. Data analysis was done using IBM SPSS version 23. A p-value of less than 0.005 at confidence interval of 95% was considered significant.  ResultsOut of 8758 specimens submitted, 534 (6.1%) were breast lesions; patients’ median age was 29 years, with mean age for benign and malignant lesions being 27 and 50 years respectively, female to male ratio was 25:1. The common symptoms were; painless lumps, breast ulceration/skin changes and breast pain in 66.8%, 15.8% and 5.4%, respectively. Fibroadenoma (54.6%), mastitis/ductal ectasia (15.8%), fibrous mastopathy (7.7%) and fibrocystic changes (5.4%) were the commonest benign lesions. Infiltrative ductal carcinoma not specified was the leading malignant histopathology (71.8%), most were poorly differentiated (74.4%) affecting young and middle aged patients (26-50 years). Lobular carcinoma (38.3%) was the leading malignancy in other histological types, followed by comedocarcinoma (10.5%) and aprocrine carcinoma (8.4%). ConclusionBenign breast lesions were the most common in this facility, most of which were fibroadenoma. Malignant tumors presented late and were predominantly poor differentiated infiltrative type, preferentially affecting young adults. An effort to enhance early detection for timely management is encouraged, given the aggressive nature of the disease.Key Words: Breast Lesions, Clinical Presentation, Pattern, Cytology and Histopathology.